Transmisor – Receptor de ECG para el Diagnóstico de Infarto al Miocardio - Gutierrez Aldana, A.; Hernández Rodríguez, P. R.; Lara Barrón, M.; Ramos Corrales, M. A.; Medécigo Micete, J. M. (Revista Mexicana de Ingenieria Biomedica, 1998)
In order to improve diagnosis and medical assistance on patients suffering a myocardial infarction, a transceiver for ECG was developed. The equipment uses a commuter line. The ECG signal is obtained from a commercial electrocardiograph and it is digitized for transmission. Two kinds of transmitters were designed: the former, was based on a PC and the later was customized with a microcontroller-based design. A PC-based system is used as a receiver in both cases. Each transmission includes a 12 lead ECG and clinical data for diagnostic purposes to determine the convenience of the thrombolytic therapy application. Results of 140 transmissions performed between an emergency room of a general hospital and a coronary care unit of a hospital with an advising medical staff are reported in this work.